OFDM/OQAM modulation for efficient dynamic spectrum access. (1st January 2012) - Skrzypczak, A.; Palicot, J.; Siohan, P.
The cognitive radio idea consists in the exploitation of spectral resources that are unused by a licensed user within a telecommunication standard. After having detected these available frequency bands by some sensing technique, our work takes a stand on the spectrum access problem. This issue requires some constraints on the modulation that must be taken into account. The flexibility in frequency offered by a multicarrier modulation (MCM) then represents a strong advantage which, in addition, can be fully exploited by the OFDM/OQAM modulation. Indeed, the fact that well localised frequency pulse shapes can be employed makes this modulation attractive for an optimised dynamic spectrum insertion. OFDM/OQAM and OFDM-based solutions are finally tested considering two different transmission scenarios. In both scenarios, it is shown that, for OFDM/OQAM, the time-frequency localisation criterion leads to a short prototype filter, satisfying a good compromise in terms of complexity/performance and also leads at the same time to a better peak-to-average power ratio (PAPR) distribution when compared to an analogue windowed OFDM scheme.